Time-saving effects using helicopter transportation: comparison to a ground transportation time predicted using a social navigation software. Issue 27 (9th July 2021) - Jang, Ji Young; Kwon, Woo-Keun; Roh, Haewon; Moon, Jong Ha; Hwang, Jun Seong; Kim, Yoon Jic; Kim, Jang Hun
Abstract : Abstract: Previous comparison studies regarding 2 types of transportation, helicopter (HEMS) versus ground emergency medical services (GEMS), have shown underlying heterogeneity as these options have completely different routes and consequent times with reference to one patient. To compare the 2 types of transportation on a case-by-case basis, we analyzed the retrospectively reviewed HEMS and predicted GEMS data using an open-source navigation software. Patients transferred by military HEMS from 2016 to 2019 were retrospectively enrolled. The HEMS records on the time of notification, injury point and destination address, and time required were reviewed. The GEMS data on distance and the predicted time required were acquired using open-source social navigation systems. Comparison analyses between the two types of transportation were conducted. Furthermore, linear logistic regression analyses were performed on the distance and time of the two options. A total of 183 patients were enrolled. There was no statistical difference ( P  = .3021) in the distance between the 2 types of transportation, and the HEMS time was significantly shorter than that of GEMS (61.31 vs 116.92 minutes, P  < .001). The simple linear curves for HEMS and GEMS were separately secured, and two graphs presented the statistical significance ( P ) as well as reasonable goodness-of-fit ( R 2 ). In general, the HEMS graph demonstrates a more gradual slope and narrow distribution compared to that of GEMS. Ideally, HEMS is identified as a better transportation modality because it has a shorter transportation time (56 minutes saved) and a low possibility of potential time delays (larger R 2 ). With a strict patient selection, HEMS can rescue injured or emergent patients who are "out of the golden hour."